Heavy smoking increases early mortality risk in patients with hepatocellular carcinoma after curative treatment - Jaejun Lee; Jong Young Choi; Soon Kyu Lee (Korean Liver Cancer Association, 2024)
Backgrounds/Aims Although cigarette smoking has been associated with an increased risk of hepatocellular carcinoma (HCC), its association with HCC mortality remains underexplored. We aimed to evaluate the effect of smoking on early mortality in HCC patients following curative treatment. Methods Data from the Korean Primary Liver Cancer Registry were examined for HCC patients who underwent liver resection or radiofrequency ablation between 2015 and 2018. Smoking cumulative dose was assessed in pack-years. The primary outcome was the 3-year overall survival (OS). Results Among 1,924 patients, 161 were classified as heavy smokers (≥40 pack-years). Heavy smokers exhibited a lower 3-year survival rate (77.1%) than nonsmokers (83.3%), with a significant difference observed in the 3-year OS (P=0.016). The assessment of smoking pack-years in relation to 3-year OS revealed a dose-dependent pattern, with the hazard ratio exceeding 1.0 at 20 pack-years and continuing to rise until 40 pack-years, reaching peak at 1.21 (95% confidence interval, 1.01-1.45). Multivariate Cox-regression analysis revealed heavy smoking, age ≥60 years, underlying cirrhosis, tumor size >3 cm, vascular invasion, and Child-Pugh class B/C as risk factors for 3-year OS. Subgroup analyses of patients with a tumor size <3 cm, absence of vascular invasion, and meeting the Milan criteria also showed inferior outcomes for heavy smokers in all three subgroups. Conclusions Heavy smoking, defined as a history of >40 pack-years, was linked to poorer 3-year survival outcomes in HCC patients undergoing curative treatments, underscoring the importance of smoking cessation in this population.